Correlation of APGAR score and cord blood pH with severity of birth asphyxia and short-term outcome - Meena, Pradeep; Meena, Mahendra; Gunawat, Maheshwar (International Journal of Contemporary Pediatrics, 2017)
Background: Birth/Perinatal asphyxia is one of the common cause of neonatal morbidity and mortality. Morbidity and mortality in asphyxia depends on duration and severity of asphyxia. The present study was carried out to find out the correlation of APGAR score and cord blood pH with severity of birth asphyxia and short-term outcome. Methods: An observational hospital based prospective study was conducted at inborn NICU, of Medical College Hospital of Southern Rajasthan from March 2015 to September 2015. We enrolled total 50 inborn asphyxiated newborns as cases. The cord blood was collected immediately at delivery for measurement of cord blood arterial blood gas analysis including pH. All the enrolled cases were admitted in the NICU for treatment and observation for complication and immediate neurological outcome. All the admitted newborns were followed till discharge/death for final outcome. The correlation of APGAR score, cord blood pH and outcome was analysed statistically. Results: The mean APGAR score at 1 min, 5 min and mean cord blood pH in babies with HIE-I were 4.40±0.89, 6.80±0.45 and 7.21±0.11; HIE-II 3.70±0.67, 6.0±1.25 and 7.20±0.06; HIE-III 2.69±0.60, 3.56±0.8 and 7.03±0.11, respectively. Correlation coefficients of APGAR 1 min, 5 min and cord blood pH to predict the severity of birth asphyxia were -0.633, -0.666 and 0.624. Conclusions: Cord blood pH at birth in combination with APGAR score can be used to predict the severity of birth asphyxia and short-term outcome. APGAR score and cord blood pH are inversely related with the duration and severity asphyxia.